Enhancing Product Quality and Marketing to Compete with Similar Businesses at Panca Perkasa Coffee Milling Company - Shofa, Tahniya Nurus; Wirsa, I Nengah (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research aims to enhance Panca Perkasa Coffee Milling Company's competitiveness amidst intense competition with similar UMKMs, which has led to a decline in coffee product sales and negatively impacted the company's growth. The study identifies strengths such as affordable prices, accepted quality, consistent production capacity, and preservative-free raw materials while noting product development and monitoring weaknesses. Method: The study utilizes a mixed-method approach, combining qualitative and quantitative research designs. Data collection methods include surveys, interviews with key stakeholders, and analysis of sales and production records. Analytical techniques involve SWOT analysis to assess strengths, weaknesses, opportunities, and threats, alongside statistical methods to evaluate sales trends and customer preferences. Practical Applications: The findings suggest practical strategies for network expansion, such as forming partnerships with distributor agents and leveraging technology, especially social media, to reach broader markets and attract new customers. Additionally, maintaining price stability, improving product quality, ensuring production continuity, and introducing attractive packaging innovations are recommended to boost competitiveness. Conclusion: The study concludes that implementing the identified strategies can significantly enhance Panca Perkasa Coffee Milling Company's market presence and sales. The results highlight the importance of strategic marketing, technological utilization, and continuous product improvement in overcoming competition and fostering business growth.